Uji Beda Karakteristik Terhadap Perusahaan Financial Distress Dan Non-Financial Distress - Intan Junaedy, Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
This research aims to find out the difference in cash flow, board size, and leverage characteristic between financial distress company and non-financial distress company that proxied by Altman Z-Score. This research used samples of manufacturing companies that listed in Indonesia Stock Exchange (Bursa Efek Indonesia) in 2015-2017. Based on purposive sampling method, this research has 42 samples which is categorized as financial distress, and 42 samples which is categorized as non-financial distress. This research uses the independent samples t-test and Mann Whitney (U-test).The result of this research showed that there is a significant difference of cash flow and leverage between financially distressed company and non-financially distressed company. As for the board size, there is no significant difference between financially distressed company and non-financially distressed company